CFD simulation of HPAM EOR solutions mechanical degradation by restrictions in turbulent flow (2020)
Polymer flooding is a widely used enhanced oil recovery (EOR) technology. The purpose of the polymer is to increase water viscosity to improve reservoir sweep efficiency. However, mechanical elements of the polymer injection facilities may impact the viscosity of the polymer negatively, decreasing it drastically. Mechanical degradation of the polymer occurs in case of flow restrictions with abrupt diameter changes in valves and control systems. Such flow restrictions may induce mechanical stresses along the polymer chain, which can result in its rupture. In this research, physical experiments and numerical simulations using CFD (Computational Fluid Dynamics) were used to propose a model for estimating the mechanical degradation for the flow of polymer solutions. This technique involves the calculation of velocity gradients, pressure drawdown, and polymer degradation of the fluid through geometry restriction. The simulations were validated through polymer injection experiments. The results show that with the greater volumetric flow and lower effective diameters, there is more mechanical degradation due to polymer shearing; nonetheless, this depends on the rheology properties inherent in each polymer in an aqueous solution. This method is suitable to estimate the mechanical degradation of the polymer solution in flooding facilities and accessories. Further, the results obtained could enhance the use of the polymer, calculating its actual mechanical degradation, minimizing it, or using it to support the development of new accessories.